Concentration of nitrogen, phosphorus, potassium and calcium in the compost produced from organic Solid waste from popular markets and residences of Huaraz-Ancash (Aporte Santiaguino, 2019)
Research wants to propose quality control methodologies for the treatment of organic solid waste. It contains components rich in carbon and nitrogen that are important for the generation of a very good quality compost, this is achieved with a homogeneous mixture of these, in such a way to achieve an optimal C / N ratio in a range of 30 to 40 ( wet matter). Variants of 30 (CB), 35 (CR) and 40 (CA), low combination (CB), regular combination (CR) and High combination (CA) were proposed for the experiment to know the proportions of the treatment. The pH parameters that reach values above 8 were produced, producing precipitation of nutrients such as Potassium and Calcium, average maximum temperature at 30 °C in week 10 of the treatment; the moisture content reached up to 40 %, amount of organic matter on average 20 %, components in dry matter of Nitrogen was 1,5 % and Phosphorus a value greater than 0,5 % at the end of the composting process, the one that had the best result was the treatment AC. A germination test was performed and a plant growth was determined compared to the CAtreatment, it is concluded that theC/Ndistribution on dry basis on average 7, is adequate in quality
Keywords: composting; high loading; heaps; aeration; mixing